(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2025)
This study investigates the impact of e-service quality on customer satisfaction and loyalty in food delivery mobile applications in Saudi Arabia, emphasizing the roles of information quality, application design, payment methods, and security and privacy. Utilizing a sample of 368 participants, the research employs a quantitative approach through structured questionnaires and structural equation modeling. Findings reveal significant positive relationships between information quality, application design, and security and privacy on customer satisfaction. Notably, customer satisfaction strongly influences loyalty, highlighting its critical role in retaining customers. Conversely, payment methods did not significantly affect customer satisfaction, indicating a shift in consumer confidence towards digital payments. Additionally, the moderating role of perceived value between customer satisfaction and loyalty was not supported, suggesting that consumers prioritize immediate satisfaction over perceived long-term benefits. These insights provide valuable implications for food delivery service providers, emphasizing the need to enhance e-service quality to foster customer satisfaction and loyalty in a competitive market. Future research should explore broader geographical contexts and additional moderating Factors to deepen the understanding of consumer behavior in the food delivery sector.